Analysis of Student Cognition and Affection Styles in Malay Essay Writing in Primary Schools - Perumal, Pushpavali; Husin, Mohd Razimi; Nachiappan, Suppiah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Kajian ini bertujuan untuk menganalisis Gaya kognisi dan afeksi murid dalam penulisan karangan Bahasa Melayu. Sampel kajian melibatkan 40 orang murid dan 12 orang murid Tahun 5 untuk ditemu bual serta 2 orang guru untuk ditemu bual. Sebanyak 40 teks karangan asal murid telah dikaji dan dianalisis serta 12 orang murid ditemubual untuk mendapatkan data serta ditranskripsikan menjadi teks kajian. Teks kajian ini dianalisis dengan menggunakan kaedah Hermeneutik untuk menginterpretasi dapatan kajian. Dapatan kajian menunjukkan bahawa murid cemerlang dan sederhana boleh mengaplikasikan Gaya kognisi, afeksi dan tahap bawah sedar dalam penulisan karangan manakala murid lemah menghadapi kesukaran dalam mempraktikkan gaya kognisi,afeksi dan tahap bawah sedar dalam penulisan karangan. Analysis of Student Cognition and Affection Styles in Malay Essay Writing in Primary Schools Abstract: This study aims to analyze the cognition style and affections of students in writing Malay essays. The study sample involved 40 students and 12 Year 5 students to be interviewed and 2 teachers to be interviewed. A total of 40 original essay texts were studied and analyzed and 12 students were interviewed to obtain data and transcribed into research texts. The text of this study was analyzed using Hermeneutic methods to interpret the findings of the study. Findings show that excellent and average students can apply cognition style, affective and subconscious level in essay writing while weak students face difficulties in practicing cognition style, affective and subconscious level in essay writing. Keywords: Affective Skills, Cognition Skills, Hermeneutic Methods, Malay Essays.